2021
DOI: 10.1186/s12985-021-01526-y
|View full text |Cite
|
Sign up to set email alerts
|

Precision therapeutic targets for COVID-19

Abstract: Beginning in late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged as a novel pathogen that causes coronavirus disease 2019 (COVID-19). SARS-CoV-2 has infected more than 111 million people worldwide and caused over 2.47 million deaths. Individuals infected with SARS-CoV-2 show symptoms of fever, cough, dyspnea, and fatigue with severe cases that can develop into pneumonia, myocarditis, acute respiratory distress syndrome, hypercoagulability, and even multi-organ failure. Curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 218 publications
(180 reference statements)
0
24
0
Order By: Relevance
“…In addition to the present study, many mechanisms have been proposed as therapeutic targets in COVID-19 infection. 36 In a hypothesis published Moreover, this study found 69.8% sensitivity and 58.1% specificity at 17.2 ng/ml serum level of AnxA1 in order to predict the need for ICU treatment in patients admitted to ED, suggesting that serum AnxA1 level may be a useful biomarker in predicting the need for ICU treatment.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition to the present study, many mechanisms have been proposed as therapeutic targets in COVID-19 infection. 36 In a hypothesis published Moreover, this study found 69.8% sensitivity and 58.1% specificity at 17.2 ng/ml serum level of AnxA1 in order to predict the need for ICU treatment in patients admitted to ED, suggesting that serum AnxA1 level may be a useful biomarker in predicting the need for ICU treatment.…”
Section: Discussionmentioning
confidence: 64%
“…In addition to the present study, many mechanisms have been proposed as therapeutic targets in COVID‐19 infection. 36 In a hypothesis published by Bonavita, it was suggested that the Ac2‐26 mimetic protein of the AnxA1 protein could be a therapeutic target, especially in the treatment of severe COVID‐19 infection, and this peptide could be one of the main mediators of cytokine storm syndrome by lowering IL‐6 levels. 14 Additionally, the use of exogenous corticosteroids (especially dexamethasone) in severe/critical COVID‐19 infection has also been recommended by WHO guidelines for COVID‐19 treatment and has been put into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This type of therapy includes, for example, staying hydrated, social distancing, and monitoring vitals at home for people with mild symptoms. For more serious cases, measures include supplemental oxygen and mechanical ventilatory support, which may be needed for more severe cases [13]. Furthermore, since the beginning of the pandemic, various drugs have been examined for the potential treatment of COVID-19.…”
Section: Discussion On Treatment Approachesmentioning
confidence: 99%
“…It is considered a class I fusion protein in that it contains both a receptor-binding domain (called S1) and a domain for mediating the membrane fusion process (called S2) (White et al 2008;Xia et al 2020). The Spike of SARS-CoV-2 has become a target in the development of vaccines and therapeutic drugs for COVID-19, due both to its importance during the viral infection cycle and to its being the primary target of host immune responses (Krumm et al 2021).…”
Section: Introductionmentioning
confidence: 99%